Indlela ababunjwe ngayo abafazi kwiincwadi zedrama ZesiXhosa - Ngqase, Fikiswa Freelance; Mtuze, P. T. Umdlanga; Mkonto, B. B. Inzonzobila; Lamati, M. Indlal'inamanyala; Nami, T. A. Inxeba Lenkosi (Stellenbosch : Stellenbosch University, 2012)
Text in Xhosa.